Traditional and complementary medicine use in multiple sclerosis: A cross-sectional study (Annals of Medical Research, 2022)
Aim: This objective of this study is to determine the TCM usage rates of the MS patients who are followed up at a Tertiary Healthcare Centre, the practices they mostly prefer, their level of satisfaction from these practices and their socio-demographic characteristics which may have an impact on their preferences.Materials and Methods: This cross-sectional type study has been conducted on 107 MS patients who are followed up at a neurology clinic. The Kurtzke Expanded Disability Status Scale is used in order to assess the clinical inadequacy. The form of questionnaire conducted includes the questions asking their socio-demographic characteristics and TCM use of the patients.Results: It is found out that 29.9% of the MS patients have sought for the GETAT practice at least once, and 51.5% of them have intended to overcome the disease. The practices mostly used are cupping therapy/bloodletting, leech therapy, herbal medicines/phytotherapy, which are followed by osteopathy, ozone therapy and music treatment. 65.6% of the participants stated that they satisfied with or benefited from the TCM practices. It is found out that there is no significant difference (p>0.05) between the TCM use and the socio-demographic characteristics of the patients but a significant and inverse relationship between TCM use and their EDDS scores (p=0.010) exists.Conclusion: It is concluded that the MS patients use the TCM practices widely, stating that they benefited substantially from these practices. It is recommended that the behaviors of the patients regarding the use of these practices be examined in order to understand the efficacy of the medical treatment and management of the symptoms.
Keywords: Multiple sclerosis; Traditional medicine; Complementary medicine